Analisis debt to asset ratio, debt to equity dan net profit margin terhadap kinerja keuangan perusahaan telekomunikasi yang terdaftar di bursa efek indonesia - Hertina, Dede; Andryana, Linda (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research aimed to examine the relationship between the debt-to-asset ratio, the debt-to-equity ratio, and the net profit margin of IDX-listed telecommunications businesses throughout the period of 2018-2021. There are a total of 19 businesses in this sector, and 8 of them were selected at random to serve as the study's sample. The financial reports of IDX-listed telecoms businesses are used as a secondary source of data for this study. Quantitative descriptive methods including classical assumption testing and multiple linear regression were used for this investigation. The research indicates that for the period of 2018-2021, the financial performance of IDX-listed businesses in the telecoms industry is affected concurrently by the debt-to-asset ratio, the debt-to-equity ratio, and the net profit margin. The financial performance of businesses listed on the IDX that operate in the telecommunications industry during the period 2018-2021 is significantly impacted by the net profit margin, but is unaffected by the debt-to-assets ratio and the debt-to-equity ratio. For the period between 2018 and 2021 covered by the IDX, the return on investment generated by enterprises in the telecommunications industry is driven primarily by the net profit margin.